Qualitative Study: English Language Education Students' Perceptions of the Use of AI Technology in Academic Writing - Nanda Wati Ika Syafitri; Agus Wardhono (Journal of English Language and Education, 2026)
The integration of artificial intelligence (AI) has transformed academic writing by providing digital tools that support English as a Foreign Language (EFL) learners throughout the writing process. Among these tools, QuillBot has become one of the most widely used because it offers accessible features such as paraphrasing, grammar checking, and vocabulary enhancement that directly address common writing difficulties faced by students. This study aimed to explore English Education students’ perceptions of using QuillBot in academic writing, the features they utilized, the challenges they encountered, and its contribution to their writing development. A qualitative descriptive design was employed involving 17 fourth-semester students of the English Education Study Program at Universitas PGRI Ronggolawe (UNIROW), Tuban. Data were collected through questionnaires and semi-structured interviews and analyzed using descriptive statistics and the interactive model of Miles, Huberman, and Saldaña. The findings revealed generally positive perceptions, with students reporting improvements in grammar, vocabulary, sentence structure, paraphrasing, writing efficiency, and confidence. However, concerns regarding overdependence, originality, and academic integrity were also identified. The study contributes to the growing literature on AI-assisted writing by providing qualitative insights into students’ experiences and offers practical implications for integrating AI tools into academic writing instruction while promoting critical thinking and responsible AI use.